Sexual abuse nature and circumstances - Quimsing-Jopson, Querima (Danyag :the UPV journal of humanities and social sciences, 2005)
"Seven victims/survivors of incest/rape from the DSWD Home for Girls with a mean age of 15 years were interviewed to arrive at the circumstances surrounding the incidents. Victims/survivors of incest suffered long-term sexual abuse because the mother either does not believe the child or is not capable of doing anything about the abuse. On the other hand, circumstances include coercion and presence/absence of significant persons in the family. Coercion could be psychological, physical, or economic form. The presence of the mother is not a guarantee that incest does not occur. In cases where the victim/survivor is the youngest daughter, history of incest recorded in the family revealed where the older daughters were also earlier victims."